Anti-inflammatory Effects of Pentraxin 3 in Human Visceral Adipocytes by Reducing Reactive Oxygen Species Production - Tojo, Taiki; Yamaoka-Tojo, Minako (Cardiology and Cardiovascular Medicine, 2021)
Background: Metabolic syndrome (MetS) is associated with an increased risk of developing atherosclerotic cardiovascular diseases. Pentraxin 3 (PTX3) is an acute phase protein strongly expressed by advanced atherosclerotic lesions. Methods and Results: To determine the functional role of PTX3 in MetS patients, cultured human visceral adipocytes were treated with human recombinant PTX3 (hr- PTX3) in various conditions. Reactive oxygen species (ROS) production from differentiated adipocytes (detected by dichlorodihydrofluorescein diacetate) was markedly reduced by the treatment of hr-PTX3 (44% reduction, P < 0.01). The inhibition was dependent on the intracellular lipid contents identified by functional knock down of Niemann-Pick C1-like 1 (NPC1L1), a cholesterol transporter, using small interfering RNA. Conclusions: PTX3-induced ROS reduction in human adipocytes suggested that MetS patients with reduced levels of PTX3 are high-risk patients for cardiovascular disease. In patients with MetS, circulating levels of PTX3 may be a novel biomarker to help predict the effectiveness of total risk management for cardiovascular prevention. <gdiv></gdiv>